Alterations of Native Forests in Northern Argentine: Regulations and Compensation Mechanisms for Environmental Services - Luna, Claudia (2017)
Natural resources form the inputs of any economic activity carried out by man; but it is a reality that most native forest ecosystems in Argentina presented from serious alterations with consequent loss of biodiversity; There is no better strategy for environmental policy than that which contributes simultaneously to solve environmental problems and socio-economic with the irreplaceable state action. The objective of this work is to analyze the situation of the forests of northern Argentina after the law of minimum budgets for the environmental protection of the same, to know in depth the processes associated with its alteration; current regulations for protection and sustainable use; as well as compensation mechanisms for environmental services arising from them.